Site-selective soft X-ray absorption as a tool to study protonation and electronic structure of gas-phase DNA. Issue 20 (17th May 2021) - Wang, Xin; Rathnachalam, Sivasudhan; Bijlsma, Klaas; Li, Wen; Hoekstra, Ronnie; Kubin, Markus; Timm, Martin; von Issendorff, Bernd; Zamudio-Bayer, Vicente; Lau, J. Tobias; Faraji, Shirin; Schlathölter, Thomas
Abstract : We identify protonation sites and study the competition of statistical fragmentation with localized bond cleavage after site-selective nitrogen 1s core-excitation by mass spectrometric detection of gas-phase oligonucleotide cations. Abstract : The conformation and the electronic structure of gas-phase oligonucleotides depends strongly on the protonation site. 5′-d( F UAG) can either be protonated at the A-N1 or at the G-N7 position. We have stored protonated 5′-d( F UAG) cations in a cryogenic ion trap held at about 20 K. To identify the protonation site and the corresponding electronic structure, we have employed soft X-ray absorption spectroscopy at the nitrogen K-edge. The obtained spectra were interpreted by comparison to time-dependent density functional theory calculations using a short-range exchange correlation functional. Despite the fact that guanine has a significantly higher proton affinity than adenine, the agreement between experiment and theory is better for the A-N1 protonated system. Furthermore, an inverse site sensitivity is observed in which the yield of the nucleobase fragments that contain the absorption site appears substantially reduced, which could be explained by non-statistical fragmentation processes, localized on the photoabsorbing nucleobase.